Analisis Yuridis Faktor Terjadinya Perkawinan di Usia Dini - Sela Rahmadana Sari; Nuri Hidayati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Marriage at an early age is a phenomenon that still occurs in various parts of the world, including Indonesia. This research aims to analyze the factors that cause marriage at an early age and its juridical implications based on applicable laws and regulations. The research method used is a qualitative approach with normative juridical analysis, which involves literature study and interviews with various parties, including community leaders, parents and teenagers. The research results show that the factors causing marriage at an early age include social pressure, cultural norms, poverty and lack of education. In addition, although Law no. 16 of 2019 has set a minimum age limit for marriage, implementation of the law still faces various challenges, such as community non-compliance and lack of socialization regarding these regulations. This research recommends the need to increase public education and awareness about the negative impacts of marriage at an early age as well as strengthening the role of child protection institutions in preventing this practice. In this way, it is hoped that a safer and more supportive environment for children's development can be created.